Human leukocyte antigen class I association with occult hepatitis B virus infection in the Shaanxi Han group: Analysis at the haplotype level - Wang, Tianju; Qi, Jun; Li, Hengxin; Chen, Liping; Liu, Sheng; Shen, Chunmei (The journal of gene medicine, 2022)
Background Human leucocyte antigen (HLA) class I genes and haplotypes correlate with hepatitis B virus (HBV) infection. Occult HBV infection (OBI), a special type of chronic HBV infection, is defined as HBV surface antigen negative patients with or those without serologic markers by the means of HBV DNA detection in human plasma or in liver tissue by a diagnostic test. So far, the associations of HLA I haplotypes with OBI have not been reported previously in China. Methods A case–control study between 107 OBI subjects and 280 healthy controls from blood donors in the Blood Center of the Shaanxi Province was conducted in the present association analysis. The HLA‐A, ‐B and ‐C loci of case–control subjects were detected and genotyped by polymerase chain reaction‐sequence based typing. The HLA‐A, ‐B and ‐C haplotypic frequencies were calculated by the maximum likelihood method. Results The HLA‐A*33:03‐C*07:01G (pc = 0.039, odds ratio [OR] = 8.996, 95% confidence interval [CI] = 1.825–44.338), B*44:03‐C*07:01G (pc = 0.0069, OR = 12.000, 95% CI = 2.507–57.436) and A*33:03‐B*44:03‐C*07:01G (pc = 0.04, OR = 7.094, 95% CI = 1.387–36.288) haplotypes showed a a significant positive association with OBI. Independent effects demonstrated that HLA‐B*44:03 and HLA‐C*07:01G gave the main contribution to risk, whereas HLA‐A*33:03 was associated only by linkage disequilibrium. Conclusions This present study is the first to demonstrate that HLA I haplotypes are associated with OBI in the Shaanxi Han population. The present results suggest that HLA‐B*44:03‐C*07:01G might be a potential risk factor for OBI. Comparisons of the frequencies of HLA I haplotypes at high resolution were made between OBI from northern Chinese Han and controls. Frequencies of HLA‐A‐B, A‐C, B‐C, A‐B‐C between the OBI group (gray column) and the control group (blank column) were compared. Haplotypes with p < 0.05 in either group were shown. p values for multiple comparisons (pc) were corrected by Bonferroni correction (*pc < 0.05). Comparisons of the frequencies of HLA I haplotypes at high‐resolution between OBI from northern Chinese Han and controls. Frequencies of HLA‐A‐B, A‐C, B‐C, A‐B‐C between OBI group (gray column) and control group (blank column) were compared.